Implications for limiting visits to patients residing in hospital wards during the COVID-19 pandemic - Kamila Jaroń; Joanna Kobza; Mateusz Grajek (Kazimierz Wielki University, 2022)
The impact of COVID-19 on the healthcare system has been devastating, as the system has had to undergo major changes, including the postponement of scheduled surgeries, the admission of patients in a state of emergency, and the use of teleportation. At the same time, the COVID-19 pandemic caused restrictions on visits to hospitalized patients by relatives, despite recommendations for family visits to patients in hospitals, as an important component of quality care provided. Material and methods: The study included 198 relatives of hospitalized patients in the period from March 2020 to March 2022 in the Silesian province. To achieve the research objective, a questionnaire developed entirely by the Authors, consisting of 9 questions, was used. The questionnaire concerned the assessment of restrictions on visits to hospitalized patients by relatives during the pandemic. The survey was conducted between November 2021 and March 2022. Results: The majority of relatives (91%) indicated that they were able to contact (including by phone) the patient every day during their hospital stay. At the same time, the largest number of respondents marked the answer that visiting patients during their stay in the hospital ward was prohibited (97%). In addition, 39% of respondents answered that it was "rather bad" to restrict visits to a loved one staying in the hospital during the pandemic. Conclusions: Undoubtedly, when considering the implementation of rules restricting patient visitation during the COVID-19 pandemic, relevant authorities should carefully look at and compare the potential harm of the issued decision to restrict visitation by relatives along with the risk of virus transmission. Currently, there are insufficient studies formally assessing the effects of restrictions on patient visits by relatives. However, it is clear from the authors' survey that the majority of relatives are rather negative about the implemented restrictions on patient visits.